3D inverse method of characteristics for hypersonic bump-inlet integration. (January 2020) - Yu, Zonghan; Huang, Guoping; Xia, Chen
Abstract: Waverider-inlet integration design is an important approach to realize hypersonic flight. The inlet lip is the key factor for internal/external flow field coupling. This paper proposes a novel 3D inverse method of characteristics (MOC) to design the inlet lip with generalized 3D shock. The unit process and marching procedure of the inverse MOC in 2D and 3D focus on obtaining the unique coordinates of the solution points. The accuracy of inverse MOC is verified through its comparison with the analytical solution of a conical flow field. The approach is then applied for a hypersonic bump-inlet integration (The freestream Mach number M ∞  =  6.0 ), where the inlet lip is inversely generated by a prescribed elliptic-conical shock wave. Inviscid results reveal good performance (The mass capturing ratio φ  =  0.813, the Mach number of inlet exit M exit  =  3.71, the total pressure recovery coefficient σ  =  0.752 ). The incident shock is well attached on the inlet lip, which is of high φ. Viscous results show relatively low performance ( φ  =  0.738, M exit  =  2.94, σ  =  0.471 ), which indicates that the new method is a promising solution for the hypersonic internal/external coupling flow. Although the viscous effects should be further considered to improve the design, the proposed method can be applied to 3D surface design with generalized shock shapes. Highlights: An inverse MOC is developed to design 3D surface with generalized shock shapes. The method ensures a unique solution and high accuracy for inviscid design. The inlet mass capturing ratio is 0.813 subjected to Mach 6 non-uniform inflow. It is a promising solution for the hypersonic internal/external coupling flow.